The Protection of Investors’ Intangible Assets through Full Protection and Security Clause in Investor State Dispute Settlement - Sufa, Maulana Irfan (PT Wahana Global Education, 2025)
This paper examines the protection of investors’ intangible assets through the Full Protection and Security (FPS) clause within the Investor-State Dispute Settlement (ISDS) framework. Traditionally interpreted as an obligation to ensure physical security of investments, the FPS standard has evolved in arbitral practice to encompass legal and regulatory safeguards, including protections for intangible assets such as intellectual property rights, licenses, shares, and contractual entitlements. This expanded interpretation reflects the growing importance and vulnerability of intangible assets in modern cross-border investments. Through analysis of relevant arbitral cases and treaty texts, this study highlights the divergent views among arbitral tribunals regarding the scope of FPS and the implications for both investors and host states. The paper concludes that a clear and consistent definition of the FPS clause particularly regarding intangible asset protection is crucial to ensuring legal certainty, balancing investor rights with state regulatory autonomy, and fostering a stable investment climate.